Influence of dairy housing on freshwater usage on commercial dairies in western Kansas - Potts, J.P.; Brouk, Michael J. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2012)
Fresh water pumping records were obtained from 24 western Kansas dairy farms for a 10-year period from 2000 through 2009. Farms were divided by facility type: dry lot (DL), free stall (FS), or a combination (DL+FS). Of the facility types studied, DL averaged smaller (P < 0.05) demand for water at 52.6 gal/cow per day compared with FS at 61.3 gal/cow. Both DL and FS facilities had less water demand than the combination facilities of DL+FS at 71.1 gal/cow of water daily. In all cases, average freshwater pumping was less than the daily amount of 134.7 gal/cow commonly used in dairy facility design. The difference may result from water conservation efforts of the dairies and the efficiency gained from operating larger milking parlors.
Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy; Free stall; Dry lot; Water conversation